Assessing predictors of rheumatoid arthritis-associated interstitial lung disease using quantitative lung densitometry. (8th November 2021) - Alevizos, Michail K; Danoff, Sonye K; Pappas, Dimitrios A; Lederer, David J; Johnson, Cheilonda; Hoffman, Eric A; Bernstein, Elana J; Bathon, Joan M; Giles, Jon T
Abstract: Objective: To assess predictors of subclinical RA-associated interstitial lung disease (RA-ILD) using quantitative lung densitometry (qLD). Methods: RA patients underwent multi-detector row CT scanning at baseline and after an average of 39 months. Scans were analysed with qLD for the percentage of lung parenchyma with high attenuation areas (%HAA: the percentage of voxels of –600 to –250 Hounsfield units). Additionally, a pulmonary radiologist calculated an expert radiologist scoring (ERS) for RA-ILD features. Generalized linear models were used to identify indicators of baseline %HAA and predictors of %HAA change. Results: Baseline %HAA was assessed in 193 RA patients and 106 had repeat qLD assessment. %HAA was correlated with ERS (Spearman's rho = 0.261; P < 0.001). Significant indicators of high baseline %HAA (>10% of lung parenchyma with high attenuation) included female sex, higher pack-years of smoking, higher BMI and anti-CCP ≥200 units, collectively contributing an area under the receiver operator curve of 0.88 (95% CI 0.81, 0.95). Predictors of %HAA increase, occurring in 49% with repeat qLD, included higher baseline %HAA, presence of mucin 5B ( MUC5B ) minor allele and absence of HLA-DRB1 shared epitope (area under the receiver operator curve = 0.69; 95% CI 0.58, 0.79). The association of the MUC5B minor allele with %HAA change was higher among men and those with higher cumulative smoking. Within the group with increased %HAA, anti-CCP level was significantly associated with a greater increase in %HAA. Conclusions: %HAA, assessed with qLD, was linked to several known risk factors for RA-ILD and may represent a more quantitative method to identify RA-ILD and track progression than expert radiologist interpretation.